Tamar dan Yusuf: Perbedaan Sikap Terhadap Kasus Pelecehan Seksual Perempuan dan Laki-laki - Asnath Niwa Natar (Faculty of Theology Duta Wacana Christian University, 2023)
AbstractAnyone can experience sexual harassment, both men and women, although most victims are women and most perpetrators are men. However, sometimes, the attitude of humans and God towards male victims is different from that of female victims. There are two stories of sexual abuse in the Bible where the victims are man and woman, namely the story of Tamar, whom Amnon abused, and Joseph, whom Potiphar’s wife abused. Although these stories have similarities, there is a difference in how God treated these two victims of sexual abuse. By using qualitative research methods in the form of literature studies, I analyze why there are differences in attitudes towards them. This article uses critical feminist interpretation through a hermeneutic of suspicion or investigation to see the influence of power relations in patriarchal and kyriarchy culture in this story and togive a voice to victims of sexual harassment, especially women, so that they receive gender justice treatment, not only from humans but also from God. AbstrakSiapa pun bisa mengalami pelecehan seksual, baik laki-laki maupun perempuan, walau kebanyakan korban adalah perempuan dan kebanyakan pelaku adalah laki-laki. Namun kadang sikap manusia dan Allah terhadap korban laki-laki berbeda dengan korban perempuan. Ada dua kisah pelecehan seksual dalam Alkitab yang korbannya adalah laki-laki dan perempuan, yaitu kisah Tamar yang dilecehkan oleh Amnon dan kisah Yusuf yang dilecehkan istri Potifar. Meskipun kisah-kisah ini memiliki kesamaan, namun terdapat perbedaan sikap Allah terhadap kedua korbanpelecehan seksual tersebut. Dengan menggunakan metode penelitian kualitatif dalam bentuk studi literatur, saya menganalisa mengapa terdapat perbedaan sikap terhadap mereka. Tulisan ini menggunakan tafsir feminis kritis melalui hermeneutik kecurigaan atau investigasi, untuk melihat pengaruh relasi kuasa dalam budaya patriarkhi dan kyriarkhi dalam kisah ini serta memberi suara pada korban-korban pelecehan seksual secara khusus perempuan sehingga mendapatkan perlakuan yang adil gender, tidak saja dari sesama manusia tetapi juga dari Allah.